A conceptual framework to examine the role of information systems quality in work life balance and employee performance (research in progress) / Sharmini. Gopinathan and Murali Raman - Gopinathan, Sharmini.; Raman, Murali (2014)
The challenges of amalgamating work and family life is an obvious fact due to technological advancement which allows remote working. A well-balanced career and social obligations are enforced as part of the human resource initiatives to maintain a healthy and committed work force in some companies abroad. This study aims to bridge the gap in the body of literature pertaining to information system quality’s impact on work life balance and employee performance in Malaysian ICT environment. The project intends to ascertain if work life balance has a mediating relationship between information system quality and employee performance. The objectives are to examine the role of information system quality (ISQ) in work life balance and determine the impact of work life balance (WLB) on employee performance. The study will be conducted with a positivist approach in mind. An integrated outline will be developed based on interviews with employees working in a remote environment from selected companies that has embarked on providing services in a 24/7 operations together with theories pertaining to ISQ and WLB from prior work drawing on multiple theoretical perspective. The findings of this study will be helpful in fostering new tools and technologies that are driven by ISQ dimensions which can be useful to formulate recommendations to the ICT sector on issues pertaining to sustainable development/policy formulation with reference to WLB. Therefore, this will indirectly empower people in the ICT sector to work remotely thus addressing pressing issues such as traffic congestion, social-family co-evolution.